Vascular Permeability and Remodelling Coincide with Inflammatory and Reparative Processes after Joint Bleeding in Factor VIII-Deficient Mice - Cooke, Esther J.; Zhou, Jenny Y.; Wyseure, Tine; Joshi, Shweta; Bhat, Vikas; Durden, Donald L.; Mosnier, Laurent O.; von Drygalski, Annette (Thrombosis and Haemostasis, 2018)
Vascular remodelling is a prominent feature of haemophilic arthropathy (HA) that may underlie re-bleeding, yet the nature of vascular changes and underlying mechanisms remain largely unknown. Here, we aimed to characterize synovial vascular remodelling and vessel integrity after haemarthrosis, as well as temporal changes in inflammatory and tissue-reparative pathways. Thirty acutely painful joints in patients with haemophilia (PWH) were imaged by musculoskeletal ultrasound with Power Doppler (MSKUS/PD) to detect vascular abnormalities and bloody effusions. Nineteen out of 30 painful joint episodes in PWH were associated with haemarthrosis, and abnormal vascular perfusion was unique to bleeding joints. A model of induced haemarthrosis in factor VIII (FVIII)-deficient mice was used for histological assessment of vascular remodelling (α-smooth muscle actin [αSMA] expression), and monitoring of in vivo vascular perfusion and permeability by MSKUS/PD and albumin extravasation, respectively. Inflammatory (M1) and reparative (M2) macrophage markers were quantified in murine synovium over a 10-week time course by real-time polymerase chain reaction. The abnormal vascular perfusion observed in PWH was recapitulated in FVIII-deficient mice after induced haemarthrosis. Neovascularization and increased vessel permeability were apparent 2 weeks post-bleed in FVIII-deficient mice, after a transient elevation of inflammatory macrophage M1 markers. These vascular changes subsided by week 4, while vascular remodelling, evidenced by architectural changes and pronounced αSMA expression, persisted alongside a reparative macrophage M2 response. In conclusion, haemarthrosis leads to transient inflammation coupled with neovascularization and associated vascular permeability, while subsequent tissue repair mechanisms coincide with vascular remodelling. Together, these vascular changes may promote re-bleeding and HA progression.
Keywords: haemarthrosis; vascular remodelling; vascular permeability; inflammation; tissue repair